Developing a novel computational model to quantify predictors of sustainable food choice - Katie L. Edwards; Lei Zhang; Annika N. Flynn; Kübra Fethiye Karataş; René Lion; Elizabeth H. Zandstra; Jeffrey M. Brunstrom; Suzanne Higgs (Food Quality and Preference, 2026)

A submerged speleothem record from Cozumel Island: insights into Mexican Caribbean climate variability during the last deglaciation - Daisy Valera-Fernández; Rafael López-Martínez; Fernando Gázquez; Miguel Bartolomé; Ana Moreno; Eneko Iriarte; Juan Luis Bernal-Wormull; Lawrence Edwards; Hai Cheng; Elizabeth Solleiro-Rebolledo; Juan Pablo Bernal-Uruchurtu; Liliana Corona-Martínez; et al. (Quaternary Science Reviews, 2026)

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

The Meanings and Dividends of Man the Hunter - Vivek V. Venkataraman; Edward H. Hagen; Duncan Stibbard-Hawkes; Raymond Hames; Sheina Lew-Levy; Haneul Jang; Luke Glowacki; Jordie Hoffman; Karen Kramer; Helen Elizabeth Davis; Kathrine Starkweather; Barry Hewlett; et al. (Evolution and Human Behavior, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Algal Symbionts Indicate Heatwave Vulnerability in Corals From Hotspots but Not From Thermal Refugia - Daisy Buzzoni; Liam Lachs; Elizabeth Beauchamp; Leah Bukurou; John Bythell; Alasdair J. Edwards; Yimnang Golbuu; Adriana Humanes; Helios M. Martinez; Geory Mereb; Julia K. Baum; James R. Guest (Molecular Ecology, 2026)
Reef‐building corals face continued declines due to climate change‐amplified marine heatwaves. In addition to affecting coral heat tolerance, corals' algal endosymbionts (family Symbiodiniaceae) can reflect their prior heatwave exposure, although understanding is often limited to heatwave‐induced shifts between symbiont genera. Here, we used ITS2 metabarcoding to characterise Symbiodiniaceae assemblages in 293 individuals of the common Indo‐Pacific coral Acropora aff. digitifera in Palau (Western Pacific), between two outer‐reef regions with contrasting heatwave histories. During the strongest recorded heatwaves, southwestern ‘hotspot’ reefs have typically accrued an additional 2°C‐weeks of heat stress compared to thermal ‘refugia’ located 60 km north. In contrast to previous studies that observed declines in symbiont richness following heat stress, we found a greater diversity of symbiont taxa and low‐abundance sequence variants in ‘hotspot’ corals, predominantly within the C40 lineage in genus Cladocopium . Combining these data with experimental heatwave performance from 168 of these corals revealed that approximately 10% of heat tolerance variability at hotspot reefs was associated with hosting different symbiont taxa. Compared to other hotspot corals, those hosting symbionts with the C15h sequence variant suffered bleaching mortality at 0.8°C‐weeks lower heat stress. Despite higher variability in heat tolerance among corals from thermal refugia compared to hotspot reefs, we found no association between heat tolerance and the symbionts hosted by refugium corals. As the world's coral reefs are exposed to intensifying marine heatwaves under accelerating climate change, the low‐abundance variants that characterise symbionts within genera or lineages may become increasingly important indicators of poor heatwave tolerance.

Recent Advancements in the Fisheries By-Products Processing Technologies as Sustainable Feedstuff for Aquaculture: Current Knowledge and Future Perspectives - Donald Torsabo; Elizabeth Pius Danba; Edward Terhemen Akange; Hidir Ariffin; Rendani Luthada-Raswiswi; Jeremiah Olanipekun Jimoh; Asuwaju Femi Pius; Sairatul Dahlianis Ishak; Noordiyana Mat Noordin (Journal of Aquatic Food Product Technology, 2025)

Designing a blended microbial culture to bioremediate distinct environmental matrices from a complex industrial site contaminated with amino-, nitro-, and chloroaromatic compounds - Isabelle Câmara; Natanna Melo; Line Lomheim; E. Erin Mack; Elizabeth A. Edwards; Jim C. Spain; Osmar Menezes; Savia Gavazza (Environmental Research, 2025)

Modeling and optimization of bioproduct formation with purple phototrophic bacteria using machine learning - Germán Buitrón; Torsten Meyer; Elizabeth A. Edwards; Virginia Montiel-Corona (Bioresource Technology, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

The mite fauna (Arachnida: Acari) of Gough Island, South Atlantic Ocean: natural colonization, endemism and human introduction - David J. Marshall; Elizabeth A. Hugo-Coetzee; Louise Coetzee; Edward A. Ueckermann; Owen Seeman; Steven L. Chown (Polar Biology, 2025)

A data-driven index for evaluating BMP water quality performance - Elizabeth A. Fassman-Beck; Edward D. Tiernan; Ka Lun Cheng; Kenneth C. Schiff (Water Research, 2025)

The Southern Ocean Time Series: a climatological view of hydrography, biogeochemistry, phytoplankton community composition, and carbon export in the Subantarctic Zone - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Ruth S. Eriksen; Peter Jansen; Xiang Yang; Gemma Woodward; Diana Davies (Ocean Science, 2025)
The Southern Ocean Time Series (SOTS) provides highly temporally resolved observations of the physical, chemical, and biological variability in the upper ocean, as well as the export of particulate organic and inorganic carbon to the ocean interior, in the subantarctic region south of Australia. The SOTS observatory focuses on the subantarctic region because of its importance in the formation of mode water and the associated uptake and storage of anthropogenic heat and carbon. The region is also critical for the supply of oxygen to the ocean interior and the export of nutrients to fuel primary production in broad areas of the low-latitude global ocean. The SOTS observatory is the longest running multidisciplinary initiative in the open Southern Ocean and has delivered high-quality observations from the surface to the seafloor for more than a decade and, for some parameters, for over two decades, using two deep-water moorings. The moorings are serviced annually, providing additional opportunities for shipboard sampling and sensor validation and calibration. Using observations collected at the SOTS site between 1997 and 2022, we present the seasonal variability in upper-ocean hydrography, biogeochemistry, phytoplankton and microplankton community composition, and diversity, along with particulate organic and particulate inorganic carbon export to the deep ocean. This climatological view of the region is complemented by a review of recent findings underpinned by observations collected by the SOTS observatory and highlighting the ongoing need for long time series to better understand the Subantarctic Ocean and its response to a changing climate.

Effects of anaerobic digestion on the dewaterability of sonicated biosludge - Sergio Luna Nino; Torsten Meyer; Elizabeth A. Edwards; D. Grant Allen (Journal of Environmental Management, 2025)

Putting numbers to a metaphor: A Bayesian Belief Network with which to infer Soil Quality and Health - Kirsty L. Hassall; Joanna Zawadzka; Alice E. Milne; Ronald Corstanje; James A. Harris; A. Gordon Dailey; Aidan M. Keith; Margaret J. Glendining; S.P. McGrath; Lindsay C. Todman; Paul Alexander; Philippa Arnold; et al. (European Journal of Agronomy, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Volcanoes of the World database - Benjamin J. Andrews; Edward Venzke; Elizabeth Cottrell; Sally S. K. Sennert; Kadie L. Bennis; A. E. J. Crafford (Bulletin of Volcanology, 2025)

Evaluating the role of moonlight-darkness dynamics as proximate spawning cues in an Acropora coral - Rubén de la Torre Cerro; Elizabeth Beauchamp; Daisy Buzzoni; Jamie Craggs; Holly East; Alasdair Edwards; Yimnang Golbuu; Adriana Humanes; Liam Lachs; Helios Martínez; Aileen Mill; Eveline van der Steeg; et al. (Coral Reefs, 2025)
For sessile broadcast spawning marine invertebrates, such as corals, successful sexual reproduction depends on conspecifics spawning synchronously. The precise monthly, lunar, and diel timing and the extent of synchrony, i.e., proportion of population reproducing at the same time, are likely to play a key role in coral population recovery, persistence, and adaptation. Despite its importance, the mechanisms by which different environmental factors trigger corals to spawn on specific dates within the lunar cycle remain poorly understood. Periods of darkness post-sunset around full moon of the spawning month have been shown to induce spawning in merulinid corals, whereas for Acropora, moonlight is considered the main determinant driver of night of spawning. Here, we conducted two manipulative field experiments around full moon in Palau using the common table coral Acropora aff. hyacinthus to disentangle the role of moonlight and darkness post-sunset as proximate cues. Coral fragments were assigned to three treatments providing different post-sunset darkness conditions, versus control and procedural control fragments exposed to natural conditions. In contrast to previous studies on Acropora , we found that Acropora aff. hyacinthus can spawn synchronously in the absence of moonlight during the nights leading to spawning. Corals exposed to darkness post-sunset for at least two to three consecutive nights advanced their spawning compared to controls. This finding indicates that periods of darkness post-sunset can act as an inducer for spawning in Acropora as well as in merulinid corals, suggesting that this mechanism may be more widespread than previously thought.

Machine learning on national shopping data reliably estimates childhood obesity prevalence and socio-economic deprivation - Gavin Long; Georgiana Nica-Avram; John Harvey; Evgeniya Lukinova; Roberto Mansilla; Simon Welham; Gregor Engelmann; Elizabeth Dolan; Kuzivakwashe Makokoro; Michelle Thomas; Edward Powell; James Goulding (Food Policy, 2025)

Vulnerability assessment of elasmobranch species to fisheries in coastal Kenya: Implications for conservation and management policies - Benedict Kiilu; Boaz Kaunda-Arara; Remmy Oddenyo; Gladys Okemwa; Elizabeth Mueni; Peter Musembi; Bernerd Fulanda; Lameck Menya-Otieno; Maurine Okeri; Grace Nduku; Jonathan Musembei; Mohamed Omar; et al. (Marine Policy, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Canopy complexity drives positive effects of tree diversity on productivity in two tree diversity experiments - Catherine Fahey; Dennis Choi; Jianmin Wang; Grant M. Domke; Joseph D. Edwards; Songlin Fei; Stephanie N. Kivlin; Elizabeth A. LaRue; Melissa K. McCormick; William J. McShea; Richard P. Phillips; Jamie Pullen; et al. (Ecology, 2025)
Forest canopy complexity (i.e., the three‐dimensional structure of the canopy) is often associated with increased species diversity as well as high primary productivity across natural forests. However, canopy complexity, tree diversity, and productivity are often confounded in natural forests, and the mechanisms of these relationships remain unclear. Here, we used two large tree diversity experiments in North America to assess three hypotheses: (1) increasing tree diversity leads to increased canopy complexity, (2) canopy complexity is positively related to tree productivity, and (3) the relationship between tree diversity and tree productivity is indirect and driven by the positive effects of canopy complexity. We found that increasing tree diversity from monocultures to mixtures of 12 species increases canopy complexity and productivity by up to 71% and 73%, respectively. Moreover, structural equation modeling indicates that the effects of tree diversity on productivity are indirect and mediated primarily by changes in internal canopy complexity. Ultimately, we suggest that increasing canopy complexity can be a major mechanism by which tree diversity enhances productivity in young forests.

Small grants advance global ocean conservation and management equity - Elizabeth H. Stephenson; Bess-Lyn Edwards; Emily Duwan; Benny Berger; Asha de Vos; Kerstin Forsberg; Nelly Isigi Kadagi; Michael F. Tlusty; Jessica V. Redfern (Biological Conservation, 2024)

Influence of Rivers, Tides, and Tidal Wetlands on Estuarine Carbonate System Dynamics - Fei Da; Marjorie A. M. Friedrichs; Pierre St-Laurent; Raymond G. Najjar; Elizabeth H. Shadwick; Edward G. Stets (Estuaries and Coasts, 2024)
Variations in estuarine carbonate chemistry can have critical impacts on marine calcifying organisms, yet the drivers of this variability are difficult to quantify from observations alone, due to the strong spatiotemporal variability of these systems. Terrestrial runoff and wetland processes vary year to year based on local precipitation, and estuarine processes are often strongly modulated by tides. In this study, a 3D-coupled hydrodynamic-biogeochemical model is used to quantify the controls on the carbonate system of a coastal plain estuary, specifically the York River estuary. Experiments were conducted both with and without tidal wetlands. Results show that on average, wetlands account for 20–30% of total alkalinity (TA) and dissolved inorganic carbon (DIC) fluxes into the estuary, and double-estuarine CO 2 outgassing. Strong quasi-monthly variability is driven by the tides and causes fluctuations between net heterotrophy and net autotrophy. On longer time scales, model results show that in wetter years, lower light availability decreases primary production relative to biological respiration (i.e., greater net heterotrophy) resulting in substantial increases in CO 2 outgassing. Additionally, in wetter years, advective exports of DIC and TA to the Chesapeake Bay increase by a factor of three to four, resulting in lower concentrations of DIC and TA within the estuary. Quantifying the impacts of these complex drivers is not only essential for a better understanding of coastal carbon and alkalinity cycling, but also leads to an improved assessment of the health and functioning of coastal ecosystems both in the present day and under future climate change.

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Changes in microbial communities during high-rate microbial selenate reduction in an up-flow anaerobic fluidized bed reactor - Su Yan; Ka Yu Cheng; Tsing Bohu; Maneesha P. Ginige; Christina Morris; Line Lomheim; Ivy Yang; Elizabeth Edwards; Guanyu Zheng; Lixiang Zhou; Anna H. Kaksonen (Chemosphere, 2024)

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Identification of environmental and methodological factors driving variability of Pepper Mild Mottle Virus (PMMoV) across three wastewater treatment plants in the City of Toronto - Eyerusalem Goitom; Sarah Ariano; Kim Gilbride; Minqing Ivy Yang; Elizabeth A. Edwards; Hui Peng; Nora Dannah; Farnaz Farahbakhsh; Eden Hataley; Hooman Sarvi; Jianxian Sun; Hassan Waseem; et al. (Science of The Total Environment, 2024)

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Long- and short-term soil storage methods other than freezing can be useful for DNA-based microbial community analysis - Joseph D. Edwards; Sarah J. Love; Richard P. Phillips; Songlin Fei; Grant Domke; John D. Parker; Melissa McCormick; Elizabeth A. LaRue; Jennifer A. Schweitzer; Joseph K. Bailey; James Fordyce; Stephanie N. Kivlin (Soil Biology and Biochemistry, 2024)

Air pollution, APOE genotype and risk of dementia among individuals with cardiovascular diseases: A population-based longitudinal study - Fei Tian; Zhengmin Qian; Zilong Zhang; Yuewei Liu; Gan Wu; Chongjian Wang; Stephen Edward McMillin; Elizabeth Bingheim; Hualiang Lin (Environmental Pollution, 2024)

Time outdoors and residential greenness are associated with reduced systemic inflammation and allostatic load - Andrey I. Egorov; Shannon M. Griffin; Jennifer N. Styles; Jason Kobylanski; Jo Klein; Lindsay Wickersham; Rebecca Ritter; Elizabeth Sams; Edward E. Hudgens; Timothy J. Wade (Environmental Pollution, 2024)

Saltwater intrusion and sea level rise threatens U.S. rural coastal landscapes and communities - Kiera L. O’Donnell; Emily S. Bernhardt; Xi Yang; Ryan E. Emanuel; Marcelo Ardón; Manuel T. Lerdau; Alex K. Manda; Anna E. Braswell; Todd K. BenDor; Eric C. Edwards; Elizabeth Frankenberg; Ashley M. Helton; et al. (Anthropocene, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Functional screening pipeline to uncover laccase-like multicopper oxidase enzymes that transform industrial lignins - Anupama A. Sharan; Annie Bellemare; Marcos DiFalco; Adrian Tsang; Thu V. Vuong; Elizabeth A. Edwards; Emma R. Master (Bioresource Technology, 2024)

Compatibility of polar organic chemical integrative sampler (POCIS) with compound specific isotope analysis (CSIA) of substituted chlorobenzenes - Shamsunnahar Suchana; Elizabeth Edwards; E. Erin Mack; Line Lomheim; Natanna Melo; Sávia Gavazza; Elodie Passeport (Science of The Total Environment, 2024)

Reinstatement and expansion of the genus Anatherum (Andropogoneae, Panicoideae, Poaceae) - Maria S. Vorontsova; Kurt B. Petersen; Patrick Minx; Taylor M. Aubuchon-Elder; M. Cinta Romay; Edward S. Buckler; Elizabeth A. Kellogg (Systematics and Biodiversity, 2023)

Temporal Patterns of Diet and Physical Activity and of Diet Alone Have More Numerous Relationships With Health and Disease Status Indicators Compared to Temporal Patterns of Physical Activity Alone - Luotao Lin; Jiaqi Guo; Anindya Bhadra; Saul B. Gelfand; Edward J. Delp; Elizabeth A. Richards; Erin Hennessy; Heather A. Eicher-Miller (Journal of the Academy of Nutrition and Dietetics, 2023)

Abrupt permafrost thaw drives spatially heterogeneous soil moisture and carbon dioxide fluxes in upland tundra - Heidi Rodenhizer; Susan M. Natali; Marguerite Mauritz; Meghan A. Taylor; Gerardo Celis; Stephanie Kadej; Allison K. Kelley; Emma R. Lathrop; Justin Ledman; Elaine F. Pegoraro; Verity G. Salmon; Christina Schädel; et al. (Global Change Biology, 2023)
Permafrost thaw causes the seasonally thawed active layer to deepen, causing the Arctic to shift toward carbon release as soil organic matter becomes susceptible to decomposition. Ground subsidence initiated by ice loss can cause these soils to collapse abruptly, rapidly shifting soil moisture as microtopography changes and also accelerating carbon and nutrient mobilization. The uncertainty of soil moisture trajectories during thaw makes it difficult to predict the role of abrupt thaw in suppressing or exacerbating carbon losses. In this study, we investigated the role of shifting soil moisture conditions on carbon dioxide fluxes during a 13‐year permafrost warming experiment that exhibited abrupt thaw. Warming deepened the active layer differentially across treatments, leading to variable rates of subsidence and formation of thermokarst depressions. In turn, differential subsidence caused a gradient of moisture conditions, with some plots becoming consistently inundated with water within thermokarst depressions and others exhibiting generally dry, but more variable soil moisture conditions outside of thermokarst depressions. Experimentally induced permafrost thaw initially drove increasing rates of growing season gross primary productivity (GPP), ecosystem respiration ( R eco ), and net ecosystem exchange (NEE) (higher carbon uptake), but the formation of thermokarst depressions began to reverse this trend with a high level of spatial heterogeneity. Plots that subsided at the slowest rate stayed relatively dry and supported higher CO 2 fluxes throughout the 13‐year experiment, while plots that subsided very rapidly into the center of a thermokarst feature became consistently wet and experienced a rapid decline in growing season GPP, R eco , and NEE (lower carbon uptake or carbon release). These findings indicate that Earth system models, which do not simulate subsidence and often predict drier active layer conditions, likely overestimate net growing season carbon uptake in abruptly thawing landscapes.

Observed amplification of the seasonal CO2 cycle at the Southern Ocean Time Series - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Richard J. Matear; Peter Jansen; Eric Schulz; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
The Subantarctic Zone, the circumpolar region of the Southern Ocean between the Subtropical and Subantarctic fronts, plays an important role in air-sea CO 2 exchange, the storage of anthropogenic CO 2 , and the ventilation of the lower thermocline. Here we use a time series from moored platforms deployed between 2011 and 2021 as part of the Southern Ocean Time Series (SOTS) observatory to investigate the seasonality and interannual variability of upper ocean hydrography and seawater CO 2 partial pressure (pCO 2 ). The region is a net sink for atmospheric CO 2 over the nearly 10-year record, with trends revealing that the ocean pCO 2 may be increasing slightly faster than the atmosphere, suggesting that oceanic as well as anthropogenic atmospheric forcing contributes to the decadal change, which includes a decline in pH on the order of 0.003 yr −1 . The observations also show an amplification of the seasonal cycle in pCO 2 , potentially linked to changes in mixed layer depth and biological productivity.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Antimicrobials and antimicrobial resistance genes in a one-year city metabolism longitudinal study using wastewater-based epidemiology - Natalie Sims; Andrew Kannan; Elizabeth Holton; Kishore Jagadeesan; Leonardos Mageiros; Richard Standerwick; Tim Craft; Ruth Barden; Edward J. Feil; Barbara Kasprzyk-Hordern (Environmental Pollution, 2023)

Microbial community dynamics in a feedback-redox controlled bioreactor process that enabled sequential selenate, nitrate and sulfate removal, and elemental selenium recovery - Su Yan; Ka Yu Cheng; Tsing Bohu; Christina Morris; Line Lomheim; Ivy Yang; Maneesha P. Ginige; Elizabeth Edwards; Guanyu Zheng; Lixiang Zhou; Anna H. Kaksonen (Journal of Water Process Engineering, 2023)

Food Insecurity and Adequacy of Dietary Intake in Youth and Young Adults With Youth-Onset Type 1 and Type 2 Diabetes - Hope Bercaw; Lauren A. Reid; Jason A. Mendoza; Edward A. Frongillo; Katherine A. Sauder; Beth A. Reboussin; Elizabeth J. Mayer-Davis; Dana Dabelea; Santica M. Marcovina; Carla Mercado; Angela D. Liese (Journal of the Academy of Nutrition and Dietetics, 2023)

Subantarctic pCO2 estimated from a biogeochemical float: comparison with moored observations reinforces the importance of spatial and temporal variability - Cathryn Ann Wynn-Edwards; Elizabeth H. Shadwick; Peter Jansen; Christina Schallenberg; Tanya Lea Maurer; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
Understanding the size and future changes of natural ocean carbon sinks is critical for the projection of atmospheric CO 2 levels. The magnitude of the Southern Ocean carbon flux has varied significantly over past decades but mechanisms behind this variability are still under debate. While high accuracy observations, e.g. from ships and moored platforms, are important to improve models they are limited through space and time. Observations from autonomous platforms with emerging biogeochemical capabilities, e.g. profiling floats, provide greater spatial and temporal coverage. However, the absolute accuracy of CO 2 partial pressure ( p CO 2 ) derived from float pH sensors is not well constrained. Here we capitalize on data collected for over a year by a biogeochemical Argo float near the Southern Ocean Time Series observatory to evaluate the accuracy of p CO 2 estimates from floats beyond the initial in water comparisons at deployment. A latitudinal gradient of increasing p CO 2 southward and spatial variability contributed to observed discrepancies. Comparisons between float estimated p CO 2 and mooring observations were therefore restricted by temperature and potential density criteria (~ 7 µatm difference) and distance (1° latitude and longitude, ~ 11 µatm difference). By utilizing high quality moored and shipboard underway p CO 2 observations, and estimates from CTD casts, we therefore found that over a year, differences in p CO 2 between platforms were within tolerable uncertainties. Continued validation efforts, using measurements with known and sufficient accuracy, are vital in the continued assessment of float-based p CO 2 estimates, especially in a highly dynamic region such as the subantarctic zone of the Southern Ocean.

Quantifying community-wide antibiotic usage via urban water fingerprinting: Focus on contrasting resource settings in South Africa - Elizabeth Holton; Carla Louw; Edward Archer; Tobias Louw; Gideon Wolfaardt; Barbara Kasprzyk-Hordern (Water Research, 2023)

Mixing cover crops suppresses weeds and roto-till reduces urban soil penetration resistance and improves infiltration - Naim Edwards; Nicholas Medina; Elizabeth Asker (Soil and Tillage Research, 2023)

An improved method for determining frequency of multiple variants of SARS-CoV-2 in wastewater using qPCR assays - Meghan Fuzzen; Nathanael B.J. Harper; Hadi A. Dhiyebi; Nivetha Srikanthan; Samina Hayat; Leslie M. Bragg; Shelley W. Peterson; Ivy Yang; J.X. Sun; Elizabeth A. Edwards; John P. Giesy; Chand S. Mangat; et al. (Science of The Total Environment, 2023)

Greener residential environment is associated with increased bacterial diversity in outdoor ambient air - Jennifer N. Styles; Andrey I. Egorov; Shannon M. Griffin; Jo Klein; J.W. Scott; Elizabeth A. Sams; Edward Hudgens; Chris Mugford; Jill R. Stewart; Kun Lu; Ilona Jaspers; Scott P. Keely; et al. (Science of The Total Environment, 2023)

Differences in the regulatory strategies of marine oligotrophs and copiotrophs reflect differences in motility - Stephen E. Noell; Elizabeth Brennan; Quinn Washburn; Edward W. Davis; Ferdi L. Hellweger; Stephen J. Giovannoni (Environmental Microbiology, 2023)
Aquatic bacteria frequently are divided into lifestyle categories oligotroph or copiotroph . Oligotrophs have proportionately fewer transcriptional regulatory genes than copiotrophs and are generally non‐motile/chemotactic. We hypothesized that the absence of chemotaxis/motility in oligotrophs prevents them from occupying nutrient patches long enough to benefit from transcriptional regulation. We first confirmed that marine oligotrophs are generally reduced in genes for transcriptional regulation and motility/chemotaxis. Next, using a non‐motile oligotroph (Ca. Pelagibacter st. HTCC7211), a motile copiotroph ( Alteromonas macleodii st. HOT1A3), and [ 14 C] l ‐alanine, we confirmed that l ‐alanine catabolism is not transcriptionally regulated in HTCC7211 but is in HOT1A3. We then found that HOT1A3 took 2.5–4 min to initiate l ‐alanine oxidation at patch l ‐alanine concentrations, compared to 4 min for chemotactic/motile cells. Thus, the time necessary for transcriptional regulation to initiate prevents transcriptional regulation from being beneficial for non‐motile oligotrophs. This is supported by a mechanistic model we developed, which predicted that HTCC7211 cells with transcriptional regulation of l ‐alanine metabolism would produce 12% of their standing ATP stock upon encountering an l ‐alanine patch, compared to 880% in HTCC7211 cells without transcriptional regulation.

In-situ multi-mode extraction (iMME) sampler for a wide-scope analysis of chemical and biological targets in water in urbanized and remote (off-the-grid) locations - Natalie Sims; Elizabeth Holton; Edward Archer; Marelize Botes; Gideon Wolfaardt; Barbara Kasprzyk-Hordern (Science of The Total Environment, 2023)

Bioaccessibility of iron in pearl millet flour contaminated with different soil types - Molly Muleya; Scott D. Young; Martin R. Broadley; Edward J.M. Joy; Prosper Chopera; Elizabeth H. Bailey (Food Chemistry, 2023)

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Changes in Southern Ocean Biogeochemistry and the Potential Impact on pH-Sensitive Planktonic Organisms - Elizabeth Shadwick; Andrés Rigual-Hernández; Ruth Eriksen; Peter Jansen; Diana Davies; Cathryn Wynn-Edwards; Adrienne Sutton; Christina Schallenberg; Thomas Trull (Oceanography, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Evidence that geographic variation in genetic ancestry associates with uterine fibroids - Jacob M. Keaton; Elizabeth A. Jasper; Jacklyn N. Hellwege; Sarah H. Jones; Eric S. Torstenson; Todd L. Edwards; Digna R. Velez Edwards (Human Genetics, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Microbial biogeography through the lens of exotic species: the recent introduction and spread of the freshwater diatom Discostella asterocostata in the United States - Andrew J. Alverson; Tyler K. Chafin; Kiley A. Jones; Kalina M. Manoylov; Hillary Johnson; Matthew L. Julius; Teofil Nakov; Elizabeth C. Ruck; Edward C. Theriot; Kevin M. Yeager; Jeffery R. Stone (Biological Invasions, 2021)

Changes in phenology and abundance of an at-risk butterfly - Rachael E. Bonoan; Elizabeth E. Crone; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

An Experimental Framework for Selectively Breeding Corals for Assisted Evolution - Adriana Humanes; Elizabeth A. Beauchamp; John C. Bythell; Mitch K. Carl; Jamie R. Craggs; Alasdair J. Edwards; Yimnang Golbuu; Liam Lachs; Helios M. Martinez; Pawel Palmowski; Faith Paysinger; Janna L. Randle; et al. (Frontiers in Marine Science, 2021)
Coral cover on tropical reefs has declined during the last three decades due to the combined effects of climate change, destructive fishing, pollution, and land use change. Drastic reductions in greenhouse gas emissions combined with effective coastal management and conservation strategies are essential to slow this decline. Innovative approaches, such as selective breeding for adaptive traits combined with large-scale sexual propagation, are being developed with the aim of pre-adapting reefs to increased ocean warming. However, there are still major gaps in our understanding of the technical and methodological constraints to producing corals for such restoration interventions. Here we propose a framework for selectively breeding corals and rearing them from eggs to 2.5-year old colonies using the coral Acropora digitifera as a model species. We present methods for choosing colonies for selective crossing, enhancing early survivorship in ex situ and in situ nurseries, and outplanting and monitoring colonies on natal reefs. We used a short-term (7-day) temperature stress assay to select parental colonies based on heat tolerance of excised branches. From six parental colonies, we produced 12 distinct crosses, and compared survivorship and growth of colonies transferred to in situ nurseries or outplanted to the reef at different ages. We demonstrate that selectively breeding and rearing coral colonies is technically feasible at small scales and could be upscaled as part of restorative assisted evolution initiatives. Nonetheless, there are still challenges to overcome before selective breeding can be implemented as a viable conservation tool, especially at the post-settlement and outplanting phases. Although interdisciplinary approaches will be needed to overcome many of the challenges identified in this study, selective breeding has the potential to be a viable tool within a reef managers toolbox to support the persistence of selected reefs in the face of climate change.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

Modelling climate change impacts on maize yields under low nitrogen input conditions in sub‐Saharan Africa - Gatien N. Falconnier; Marc Corbeels; Kenneth J. Boote; François Affholder; Myriam Adam; Dilys S. MacCarthy; Alex C. Ruane; Claas Nendel; Anthony M. Whitbread; Éric Justes; Lajpat R. Ahuja; Folorunso M. Akinseye; et al. (Global Change Biology, 2020)
Smallholder farmers in sub‐Saharan Africa (SSA) currently grow rainfed maize with limited inputs including fertilizer. Climate change may exacerbate current production constraints. Crop models can help quantify the potential impact of climate change on maize yields, but a comprehensive multimodel assessment of simulation accuracy and uncertainty in these low‐input systems is currently lacking. We evaluated the impact of varying [CO 2 ], temperature and rainfall conditions on maize yield, for different nitrogen (N) inputs (0, 80, 160 kg N/ha) for five environments in SSA, including cool subhumid Ethiopia, cool semi‐arid Rwanda, hot subhumid Ghana and hot semi‐arid Mali and Benin using an ensemble of 25 maize models. Models were calibrated with measured grain yield, plant biomass, plant N, leaf area index, harvest index and in‐season soil water content from 2‐year experiments in each country to assess their ability to simulate observed yield. Simulated responses to climate change factors were explored and compared between models. Calibrated models reproduced measured grain yield variations well with average relative root mean square error of 26%, although uncertainty in model prediction was substantial (CV = 28%). Model ensembles gave greater accuracy than any model taken at random. Nitrogen fertilization controlled the response to variations in [CO 2 ], temperature and rainfall. Without N fertilizer input, maize (a) benefited less from an increase in atmospheric [CO 2 ]; (b) was less affected by higher temperature or decreasing rainfall; and (c) was more affected by increased rainfall because N leaching was more critical. The model intercomparison revealed that simulation of daily soil N supply and N leaching plays a crucial role in simulating climate change impacts for low‐input systems. Climate change and N input interactions have strong implications for the design of robust adaptation approaches across SSA, because the impact of climate change in low input systems will be modified if farmers intensify maize production with balanced nutrient management.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Split-Brain: What We Know Now and Why This is Important for Understanding Consciousness - Edward H. F. de Haan; Paul M. Corballis; Steven A. Hillyard; Carlo A. Marzi; Anil Seth; Victor A. F. Lamme; Lukas Volz; Mara Fabri; Elizabeth Schechter; Tim Bayne; Michael Corballis; Yair Pinto (Neuropsychology Review, 2020)
Recently, the discussion regarding the consequences of cutting the corpus callosum (“split-brain”) has regained momentum (Corballis, Corballis, Berlucchi, & Marzi, Brain , 141 (6), e46, 2018; Pinto et al., Brain, 140 (5), 1231–1237, 2017a; Pinto, Lamme, & de Haan, Brain, 140 (11), e68, 2017; Volz & Gazzaniga, Brain , 140 (7), 2051–2060, 2017; Volz, Hillyard, Miller, & Gazzaniga, Brain , 141 (3), e15, 2018). This collective review paper aims to summarize the empirical common ground, to delineate the different interpretations, and to identify the remaining questions. In short, callosotomy leads to a broad breakdown of functional integration ranging from perception to attention. However, the breakdown is not absolute as several processes, such as action control, seem to remain unified. Disagreement exists about the responsible mechanisms for this remaining unity. The main issue concerns the first-person perspective of a split-brain patient. Does a split-brain harbor a split consciousness or is consciousness unified? The current consensus is that the body of evidence is insufficient to answer this question, and different suggestions are made with respect to how future studies might address this paucity. In addition, it is suggested that the answers might not be a simple yes or no but that intermediate conceptualizations need to be considered.

Bridging From Monitoring to Solutions-Based Thinking: Lessons From CalCOFI for Understanding and Adapting to Marine Climate Change Impacts - Natalya D. Gallo; Elizabeth Drenkard; Andrew R. Thompson; Edward D. Weber; Deb Wilson-Vandenberg; Sam McClatchie; J. Anthony Koslow; Brice X. Semmens (Frontiers in Marine Science, 2019)

Modeling Environmental DNA Transport in the Coastal Ocean Using Lagrangian Particle Tracking - Elizabeth A. Andruszkiewicz; Jeffrey R. Koseff; Oliver B. Fringer; Nicholas T. Ouellette; Anna B. Lowe; Christopher A. Edwards; Alexandria B. Boehm (Frontiers in Marine Science, 2019)

An Integrated Data Analytics Platform - Edward M. Armstrong; Mark A. Bourassa; Thomas A. Cram; Maya DeBellis; Jocelyn Elya; Frank R. Greguska; Thomas Huang; Joseph C. Jacob; Zaihua Ji; Yongyao Jiang; Yun Li; Nga Quach; et al. (Frontiers in Marine Science, 2019)

Combining supervised run interval training or moderate-intensity continuous training with the diabetes prevention program on clinical outcomes - Nicole M. Gilbertson; Joan A. Mandelson; Kathryn Hilovsky; Jeremy D. Akers; Trent A. Hargens; David L. Wenos; Elizabeth S. Edwards (European Journal of Applied Physiology, 2019)

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Non-alcoholic fatty liver disease and colorectal cancer survival - Kana Wu; Mike Z. Zhai; Erin K. Weltzien; Elizabeth M. Cespedes Feliciano; Jeffrey A. Meyerhardt; Edward Giovannucci; Bette J. Caan (Cancer Causes & Control, 2019)

Current status of the Botryosphaeriaceae in Australia - Treena I. Burgess; Yu Pei Tan; Jeff Garnas; Jacqueline Edwards; Kelly A. Scarlett; Lucas A. Shuttleworth; Rosalie Daniel; Elizabeth K. Dann; Louisamarie E. Parkinson; Quang Dinh; Roger G. Shivas; Fahimeh Jami (Australasian Plant Pathology, 2019)

Evolutionarily stable communities: a framework for understanding the role of trait evolution in the maintenance of diversity - Kyle F. Edwards; Colin T. Kremer; Elizabeth T. Miller; Matthew M. Osmond; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2018)
Biological diversity depends on the interplay between evolutionary diversification and ecological mechanisms allowing species to coexist. Current research increasingly integrates ecology and evolution over a range of timescales, but our common conceptual framework for understanding species coexistence requires better incorporation of evolutionary processes. Here, we focus on the idea of evolutionarily stable communities ( ESC s), which are theoretical endpoints of evolution in a community context. We use ESC s as a unifying framework to highlight some important but under‐appreciated theoretical results, and we review empirical research relevant to these theoretical predictions. We explain how, in addition to generating diversity, evolution can also limit diversity by reducing the effectiveness of coexistence mechanisms. The coevolving traits of competing species may either diverge or converge, depending on whether the number of species in the community is low (undersaturated) or high (oversaturated) relative to the ESC . Competition in oversaturated communities can lead to extinction or neutrally coexisting, ecologically equivalent species. It is critical to consider trait evolution when investigating fundamental ecological questions like the strength of different coexistence mechanisms, the feasibility of ecologically equivalent species, and the interpretation of different patterns of trait dispersion.

Pragmatic criteria to define chronic pseudomonas aeruginosa infection among adults with cystic fibrosis - Zhe Hui Hoo; Elizabeth Coates; Chin Maguire; Hannah Cantrill; Nadia Shafi; Edward F. Nash; Angela McGowan; Stephen J. Bourke; William G. Flight; Thomas V. Daniels; Julia A. Nightingale; Mark I. Allenby; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Functional characterization of ligninolytic Klebsiella spp. strains associated with soil and freshwater - Amanda O. dos S. Melo-Nascimento; Claudia Treumann; Camila Neves; Edmilson Andrade; Ana Camila Andrade; Robert Edwards; Elizabeth Dinsdale; Thiago Bruce (Archives of Microbiology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Neural correlates of verbal memory in youth with heavy prenatal alcohol exposure - Lauren A. Gross; Eileen M. Moore; Jeffrey R. Wozniak; Claire D. Coles; Julie A. Kable; Elizabeth R. Sowell; Kenneth L. Jones; Edward P. Riley; Sarah N. Mattson (Brain Imaging and Behavior, 2018)

Variation in perception of environmental change in nine Solomon Islands communities: implications for securing fairness in community-based adaptation - Jonathan Edward Ensor; Kirsten Elizabeth Abernethy; Eric Timothy Hoddy; Shankar Aswani; Simon Albert; Ismael Vaccaro; Jason Jon Benedict; Douglas James Beare (Regional Environmental Change, 2018)

Glucosamine use and risk of colorectal cancer: results from the Cancer Prevention Study II Nutrition Cohort - Elizabeth D. Kantor; Christina C. Newton; Edward L. Giovannucci; Marjorie L. McCullough; Peter T. Campbell; Eric J. Jacobs (Cancer Causes & Control, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

Nonlinear CO 2 flux response to 7 years of experimentally induced permafrost thaw - Marguerite Mauritz; Rosvel Bracho; Gerardo Celis; Jack Hutchings; Susan M. Natali; Elaine Pegoraro; Verity G. Salmon; Christina Schädel; Elizabeth E. Webb; Edward A. G. Schuur (Global Change Biology, 2017)
Rapid Arctic warming is expected to increase global greenhouse gas concentrations as permafrost thaw exposes immense stores of frozen carbon (C) to microbial decomposition. Permafrost thaw also stimulates plant growth, which could offset C loss. Using data from 7 years of experimental Air and Soil warming in moist acidic tundra, we show that Soil warming had a much stronger effect on CO 2 flux than Air warming. Soil warming caused rapid permafrost thaw and increased ecosystem respiration (R eco ), gross primary productivity ( GPP ), and net summer CO 2 storage ( NEE ). Over 7 years R eco , GPP , and NEE also increased in Control (i.e., ambient plots), but this change could be explained by slow thaw in Control areas. In the initial stages of thaw, R eco , GPP , and NEE increased linearly with thaw across all treatments, despite different rates of thaw. As thaw in Soil warming continued to increase linearly, ground surface subsidence created saturated microsites and suppressed R eco , GPP , and NEE . However R eco and GPP remained high in areas with large Eriophorum vaginatum biomass. In general NEE increased with thaw, but was more strongly correlated with plant biomass than thaw, indicating that higher R eco in deeply thawed areas during summer months was balanced by GPP . Summer CO 2 flux across treatments fit a single quadratic relationship that captured the functional response of CO 2 flux to thaw, water table depth, and plant biomass. These results demonstrate the importance of indirect thaw effects on CO 2 flux: plant growth and water table dynamics. Nonsummer R eco models estimated that the area was an annual CO 2 source during all years of observation. Nonsummer CO 2 loss in warmer, more deeply thawed soils exceeded the increases in summer GPP , and thawed tundra was a net annual CO 2 source.

Cultivating microbial dark matter in benzene‐degrading methanogenic consortia - Fei Luo; Cheryl E. Devine; Elizabeth A. Edwards (Environmental Microbiology, 2016)
Summary The microbes responsible for anaerobic benzene biodegradation remain poorly characterized. In this study, we identified and quantified microbial populations in a series of 16 distinct methanogenic, benzene‐degrading enrichment cultures using a combination of traditional 16 S rRNA clone libraries (four cultures), pyrotag 16 S rRNA amplicon sequencing (11 cultures), metagenome sequencing (1 culture) and quantitative polymerase chain reaction ( qPCR ; 12 cultures). An operational taxonomic unit ( OTU ) from the D eltaproteobacteria designated ORM 2 that is only 84% to 86% similar to S yntrophus or D esulfobacterium spp. was consistently identified in all enrichment cultures, and typically comprised more than half of the bacterial sequences. In addition to ORM 2, a sequence belonging to P arcubacteria (candidate division OD 1) identified from the metagenome data was the only other OTU common to all the cultures surveyed. Culture transfers (1% and 0.1%) were made in the presence and absence of benzene, and the abundance of ORM 2, OD 1 and other OTUs was tracked over 415 days using qPCR . ORM 2 sequence abundance increased only when benzene was present, while the abundance of OD 1 and other OTUs increased even in the absence of benzene. D eltaproteobacterium ORM 2 is unequivocally the benzene‐metabolizing population. This study also hints at laboratory cultivation conditions for a member of the widely distributed yet uncultivated P arcubacteria ( OD 1).

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Correlates of objectively measured sedentary behavior in breast cancer survivors - Siobhan M. Phillips; Gillian R. Lloyd; Elizabeth A. Awick; Edward McAuley (Cancer Causes & Control, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

Separate and Combined Effects of Estuarine Stress Gradients and Disturbance on Oyster Population Development on Restored Reefs - Elizabeth A. Salewski; C . Edward Proffitt (Estuaries and Coasts, 2016)

Student Accomplishments in the Rapid Response Radiotherapy Program: A 10-Year Review - Rachel McDonald; Breanne Lechner; Natalie Pulenzas; Gillian Bedard; Erin Wong; Lori Holden; May Tsao; Elizabeth Barnes; Ewa Szumacher; Gonenc Fenton; Edward Chow; Marko Popovic; et al. (Journal of Cancer Education, 2015)

Fostering effective international collaboration for marine science in small island states - Edward J. Hind; Steven M. Alexander; Stephanie J. Green; Jacob P. Kritzer; Michael J. Sweet; Ayana Elizabeth Johnson; Fabian P. Amargós; Nicola S. Smith; Angelie M. Peterson (Frontiers in Marine Science, 2015)

Cardiorespiratory fitness is associated with brain structure, cognition, and mood in a middle-aged cohort at risk for Alzheimer’s disease - Elizabeth A. Boots; Stephanie A. Schultz; Jennifer M. Oh; Jordan Larson; Dorothy Edwards; Dane Cook; Rebecca L. Koscik; Maritza N. Dowling; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; et al. (Brain Imaging and Behavior, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

The complete genome sequence for putative H 2 ‐ and S ‐oxidizer C andidatus Sulfuricurvum sp., assembled de novo from an aquifer‐derived metagenome - Kim M. Handley; Daniela Bartels; Edward J. O'Loughlin; Kenneth H. Williams; William L. Trimble; Kelly Skinner; Jack A. Gilbert; Narayan Desai; Elizabeth M. Glass; Tobias Paczian; Andreas Wilke; Dionysios Antonopoulos; et al. (Environmental Microbiology, 2014)
Summary We reconstructed the complete 2.4 Mb‐long genome of a previously uncultivated epsilonproteobacterium, C andidatus Sulfuricurvum sp. RIFRC ‐1, via assembly of short‐read shotgun metagenomic data using a complexity reduction approach. Genome‐based comparisons indicate the bacterium is a novel species within the S ulfuricurvum genus, which contains one cultivated representative, S . kujiense . Divergence between the species appears due in part to extensive genomic rearrangements, gene loss and chromosomal versus plasmid encoding of certain (respiratory) genes by RIFRC ‐1. Deoxyribonucleic acid for the genome was obtained from terrestrial aquifer sediment, in which RIFRC ‐1 comprised ∼ 47% of the bacterial community. Genomic evidence suggests RIFRC ‐1 is a chemolithoautotrophic diazotroph capable of deriving energy for growth by microaerobic or nitrate‐/nitric oxide‐dependent oxidation of S 0 , sulfide or sulfite or H 2 oxidation. Carbon may be fixed via the reductive tricarboxylic acid cycle. Consistent with these physiological attributes, the local aquifer was microoxic with small concentrations of available nitrate, small but elevated concentrations of reduced sulfur and NH 4 + / NH 3 ‐limited. Additionally, various mechanisms for heavy metal and metalloid tolerance and virulence point to a lifestyle well‐adapted for metal(loid)‐rich environments and a shared evolutionary past with pathogenic E psilonproteobacteria . Results expand upon recent findings highlighting the potential importance of sulfur and hydrogen metabolism in the terrestrial subsurface.

Distinct dissolved organic matter sources induce rapid transcriptional responses in coexisting populations of P rochlorococcus , P elagibacter and the OM60 clade - Adrian K. Sharma; Jamie W. Becker; Elizabeth A. Ottesen; Jessica A. Bryant; Solange Duhamel; David M. Karl; Otto X. Cordero; Daniel J. Repeta; Edward F. DeLong (Environmental Microbiology, 2014)
Summary A considerable fraction of the E arth's organic carbon exists in dissolved form in seawater. To investigate the roles of planktonic marine microbes in the biogeochemical cycling of this dissolved organic matter ( DOM ), we performed controlled seawater incubation experiments and followed the responses of an oligotrophic surface water microbial assemblage to perturbations with DOM derived from an axenic culture of P rochlorococcus , or high‐molecular weight DOM concentrated from nearby surface waters. The rapid transcriptional responses of both P rochlorococcus and P elagibacter populations suggested the utilization of organic nitrogen compounds common to both DOM treatments. Along with these responses, both populations demonstrated decreases in gene transcripts associated with nitrogen stress, including those involved in ammonium acquisition. In contrast, responses from low abundance organisms of the NOR5/OM60 gammaproteobacteria were observed later in the experiment, and included elevated levels of gene transcripts associated with polysaccharide uptake and oxidation. In total, these results suggest that numerically dominant oligotrophic microbes rapidly acquire nitrogen from commonly available organic sources, and also point to an important role for carbohydrates found within the DOM pool for sustaining the less abundant microorganisms in these oligotrophic systems.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Association of C-peptide and leptin with prostate cancer incidence in the Health Professionals Follow-up Study - Gabriel Y. Lai; Edward L. Giovannucci; Michael N. Pollak; Sarah B. Peskoe; Meir J. Stampfer; Walter C. Willett; Elizabeth A. Platz (Cancer Causes & Control, 2014)

Population-based surveillance for cervical cancer precursors in three central cancer registries, United States 2009 - Elaine W. Flagg; S. Deblina Datta; Mona Saraiya; Elizabeth R. Unger; Edward Peters; Lauren Cole; Vivien W. Chen; Thomas Tucker; Mary Jane Byrne; Glenn Copeland; Won Silva; Meg Watson; et al. (Cancer Causes & Control, 2014)

Permafrost degradation stimulates carbon loss from experimentally warmed tundra - Susan M. Natali; Edward A. G. Schuur; Elizabeth E. Webb; Caitlin E. Hicks Pries; Kathryn G. Crummer (Ecology, 2014)
A large pool of organic carbon (C) has been accumulating in the Arctic for thousands of years because cold and waterlogged conditions have protected soil organic material from microbial decomposition. As the climate warms this vast and frozen C pool is at risk of being thawed, decomposed, and released to the atmosphere as greenhouse gasses. At the same time, some C losses may be offset by warming‐mediated increases in plant productivity. Plant and microbial responses to warming ultimately determine net C exchange from ecosystems, but the timing and magnitude of these responses remain uncertain. Here we show that experimental warming and permafrost (ground that remains below 0°C for two or more consecutive years) degradation led to a two‐fold increase in net ecosystem C uptake during the growing season. However, warming also enhanced winter respiration, which entirely offset growing‐season C gains. Winter C losses may be even higher in response to actual climate warming than to our experimental manipulations, and, in that scenario, could be expected to more than double overall net C losses from tundra to the atmosphere. Our results highlight the importance of winter processes in determining whether tundra acts as a C source or sink, and demonstrate the potential magnitude of C release from the permafrost zone that might be expected in a warmer climate.

The first engagement of partners in the E uprymna scolopes – V ibrio fischeri symbiosis is a two‐step process initiated by a few environmental symbiont cells - Melissa A. Altura; Elizabeth A. C. Heath‐Heckman; Amani Gillette; Natacha Kremer; Anne‐Marie Krachler; Caitlin Brennan; Edward G. Ruby; Kim Orth; Margaret J. McFall‐Ngai (Environmental Microbiology, 2013)
Summary We studied the E uprymna scolopes – V ibrio fischeri symbiosis to characterize, in vivo and in real time, the transition between the bacterial partner's free‐living and symbiotic life styles. Previous studies using high inocula demonstrated that environmental V . fischeri cells aggregate during a 3 h period in host‐shed mucus along the light organ's superficial ciliated epithelia. Under lower inoculum conditions, similar to the levels of symbiont cells in the environment, this interaction induces haemocyte trafficking into these tissues. Here, in experiments simulating natural conditions, microscopy revealed that at 3 h following first exposure, only ∼ 5 V . fischeri cells aggregated on the organ surface. These cells associated with host cilia and induced haemocyte trafficking. Symbiont viability was essential and mutants defective in symbiosis initiation and/or production of certain surface features, including the M am7 protein, which is implicated in host cell attachment of V . cholerae , associated normally with host cilia. Studies with exopolysaccharide mutants, which are defective in aggregation, suggest a two‐step process of V . fischeri cell engagement: association with host cilia followed by aggregation, i.e. host cell–symbiont interaction with subsequent symbiont–symbiont cell interaction. Taken together, these data provide a new model of early partner engagement, a complex model of host–symbiont interaction with exquisite sensitivity.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Genetic and physical mapping of flowering time loci in canola (Brassica napus L.) - Harsh Raman; Rosy Raman; Paul Eckermann; Neil Coombes; Sahana Manoli; Xiaoxiao Zou; David Edwards; Jinling Meng; Roslyn Prangnell; Jiri Stiller; Jacqueline Batley; David Luckett; et al. (Theoretical and Applied Genetics, 2013)

Prospective study of effect modification by Toll-like receptor 4 variation on the association between Trichomonas vaginalis serostatus and prostate cancer - Yen Ching Chen; Yi Ling Huang; Elizabeth A. Platz; John F. Alderete; Lu Zheng; Jennifer R. Rider; Peter Kraft; Edward Giovannucci; Siobhan Sutcliffe (Cancer Causes & Control, 2013)

Integrating Climate and Ocean Change Vulnerability into Conservation Planning - Elizabeth McLeod; Alison Green; Edward Game; Kenneth Anthony; Joshua Cinner; Scott F. Heron; Joanie Kleypas; Catherine E. Lovelock; John M. Pandolfi; Robert L. Pressey; Rodney Salm; Steve Schill; et al. (Coastal Management, 2012)

Functional mobility of older adults after concentric and eccentric endurance exercise - Mandy Lucinda Gault; Richard Edward Clements; Mark Elizabeth Theodorus Willems (European Journal of Applied Physiology, 2012)

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

Extensive gaps and biases in our knowledge of a well‐known fauna: implications for integrating biological traits into macroecology - Elizabeth H. M. Tyler; Paul J. Somerfield; Edward Vanden Berghe; Julie Bremner; Emma Jackson; Olivia Langmead; Maria Lourdes D. Palomares; Thomas J. Webb (Global Ecology and Biogeography, 2012)
Aim Ecologists seeking to describe patterns at ever larger scales require compilations of data on the global abundance and distribution of species. Comparable compilations of biological data are needed to elucidate the mechanisms behind these patterns, but have received far less attention. We assess the availability of biological data across an entire assemblage: the well‐documented demersal marine fauna of the United Kingdom. We also test whether data availability for a species depends on its taxonomic group, maximum body size, the number of times it has been recorded in a global biogeographic database, or its commercial and conservation importance. Location Seas of the United Kingdom. Methods We defined a demersal marine fauna of 973 species from 15 phyla and 40 classes using five extensive surveys around the British Isles. We then quantified the availability of data on eight key biological traits (termed biological knowledge) for each species from online databases. Relationships between biological knowledge and our predictors were tested with generalized linear models. Results Full data on eight fundamental biological traits exist for only 9% ( n = 88) of the UK demersal marine fauna, and 20% of species completely lack data. Clear trends in our knowledge exist: fish (median biological knowledge score = six traits) are much better known than invertebrates (one trait). Biological knowledge increases with biogeographic knowledge and (to a lesser extent) with body size, and is greater in species that are commercially exploited or of conservation concern. Main conclusions Our analysis reveals deep ignorance of the basic biology of a well‐studied fauna, highlighting the need for far greater efforts to compile biological trait data. Clear biases in our knowledge, relating to how well sampled or ‘important’ species are suggests that caution is required in extrapolating small subsets of biologically well‐known species to ecosystem‐level studies.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Temporal and spatial variation in the δ15N and δ13C values of fish and squid from Alaskan waters - Carolyn M. Kurle; Elizabeth H. Sinclair; Ann E. Edwards; Carolyn J. Gudmundson (Marine Biology, 2011)

Potentials and limitations of Coastal Web Atlases - Elizabeth K. O’Dea; Edward Dwyer; Valerie Cummins; Dawn J. Wright (Journal of Coastal Conservation, 2011)

High Performance Thin Layer Chromatography (HPTLC) profile of an insecticidal compound of Trochus radiatus and assessment of mucus-associated bacterial extracts - Mary Elizabeth K. Gnanambal; K. C. Ramya Devi; P. Hareesh Chandra; Edward J. K. Patterson (Phytoparasitica, 2011)

Chloroform respiration to dichloromethane by a Dehalobacter population - Ariel Grostern; Melanie Duhamel; Sandra Dworatzek; Elizabeth A. Edwards (Environmental Microbiology, 2010)
Summary Chloroform (CF), or trichloromethane, is an ubiquitous environmental pollutant because of its widespread industrial use, historically poor disposal and recalcitrance to biodegradation. Chloroform is a potent inhibitor of metabolism and no known organism uses it as a growth substrate. We discovered that CF was rapidly and sustainably dechlorinated in the course of investigating anaerobic reductive dechlorination of 1,1,1‐trichloroethane in a Dehalobacter ‐containing culture. Like 1,1,1‐trichloroethane dechlorination in this culture, CF dechlorination was a growth‐linked respiratory process, requiring H 2 as an electron donor and CF as an electron acceptor. Moreover, the same specific reductive dehalogenase likely catalyzed both reactions. This Dehalobacter population appears specialized for substrates with three halogen substituents on the same carbon atom, with widespread implications for bioremediation.

Metagenomic analysis of stressed coral holobionts - Rebecca Vega Thurber; Dana Willner‐Hall; Beltran Rodriguez‐Mueller; Christelle Desnues; Robert A. Edwards; Florent Angly; Elizabeth Dinsdale; Linda Kelly; Forest Rohwer (Environmental Microbiology, 2009)
Summary The coral holobiont is the community of metazoans, protists and microbes associated with scleractinian corals. Disruptions in these associations have been correlated with coral disease, but little is known about the series of events involved in the shift from mutualism to pathogenesis. To evaluate structural and functional changes in coral microbial communities, Porites compressa was exposed to four stressors: increased temperature, elevated nutrients, dissolved organic carbon loading and reduced pH. Microbial metagenomic samples were collected and pyrosequenced. Functional gene analysis demonstrated that stressors increased the abundance of microbial genes involved in virulence, stress resistance, sulfur and nitrogen metabolism, motility and chemotaxis, fatty acid and lipid utilization, and secondary metabolism. Relative changes in taxonomy also demonstrated that coral‐associated microbiota ( Archaea , Bacteria , protists) shifted from a healthy‐associated coral community (e.g. Cyanobacteria , Proteobacteria and the zooxanthellae Symbiodinium ) to a community (e.g. Bacteriodetes , Fusobacteria and Fungi ) of microbes often found on diseased corals. Additionally, low‐abundance Vibrio spp. were found to significantly alter microbiome metabolism, suggesting that the contribution of a just a few members of a community can profoundly shift the health status of the coral holobiont.

Assessing the extent and diversity of riparian ecosystems in Sonora, Mexico - Michael L. Scott; Pamela L. Nagler; Edward P. Glenn; Carlos Valdes-Casillas; Joseph A. Erker; Elizabeth W. Reynolds; Patrick B. Shafroth; Euduardo Gomez-Limon; Cory L. Jones (Biodiversity and Conservation, 2009)

Metagenomic and stable isotopic analyses of modern freshwater microbialites in Cuatro Ciénegas, Mexico - Mya Breitbart; Ana Hoare; Anthony Nitti; Janet Siefert; Matthew Haynes; Elizabeth Dinsdale; Robert Edwards; Valeria Souza; Forest Rohwer; David Hollander (Environmental Microbiology, 2009)
Summary Ancient biologically mediated sedimentary carbonate deposits, including stromatolites and other microbialites, provide insight into environmental conditions on early Earth. The primary limitation to interpreting these records is our lack of understanding regarding microbial processes and the preservation of geochemical signatures in contemporary microbialite systems. Using a combination of metagenomic sequencing and isotopic analyses, this study describes the identity, metabolic potential and chemical processes of microbial communities from living microbialites from Cuatro Ciénegas, Mexico. Metagenomic sequencing revealed a diverse, redox‐dependent microbial community associated with the microbialites. The microbialite community is distinct from other marine and freshwater microbial communities, and demonstrates extensive environmental adaptation. The microbialite metagenomes contain a large number of genes involved in the production of exopolymeric substances and the formation of biofilms, creating a complex, spatially structured environment. In addition to the spatial complexity of the biofilm, microbial activity is tightly controlled by sensory and regulatory systems, which allow for coordination of autotrophic and heterotrophic processes. Isotopic measurements of the intracrystalline organic matter demonstrate the importance of heterotrophic respiration of photoautotrophic biomass in the precipitation of calcium carbonate. The genomic and stable isotopic data presented here significantly enhance our evolving knowledge of contemporary biomineralization processes, and are directly applicable to studies of ancient microbialites.

Prevalence and predictors of cancer screening among American Indian and Alaska native people: the EARTH study - Mary Catherine Schumacher; Martha L. Slattery; Anne P. Lanier; Khe-Ni Ma; Sandra Edwards; Elizabeth D. Ferucci; Lillian Tom-Orme (Cancer Causes & Control, 2008)

Dynamics of T cell memory in human cytomegalovirus infection - Edward C. P. Waller; Elizabeth Day; J. G. Patrick Sissons; Mark R. Wills (Medical Microbiology and Immunology, 2008)

Isotope analysis as a natural reaction probe to determine mechanisms of biodegradation of 1,2‐dichloroethane - Sarah K. Hirschorn; M. Joyce Dinglasan‐Panlilio; Elizabeth A. Edwards; Georges Lacrampe‐Couloume; Barbara Sherwood Lollar (Environmental Microbiology, 2007)
Summary 1,2‐Dichloroethane (1,2‐DCA), a chlorinated aliphatic hydrocarbon, is a well‐known groundwater contaminant. In this study, fractionation of stable carbon isotope values of 1,2‐DCA during biodegradation was used as a novel reaction probe to provide information about the mechanism of 1,2‐DCA biodegradation under both aerobic (O 2 ‐reducing) and anaerobic (NO 3 ‐reducing) conditions. Under O 2 ‐reducing conditions, an isotopic enrichment value ( ε ) of −25.8 ± 1.1‰ (±95% confidence intervals) was measured for the enrichment culture. Under NO 3 ‐reducing conditions, an ε ‐value of −25.8 ± 3.5‰ was measured. The microbial culture produced isotopic enrichment values ( ε ) that are not only large and reproducible, but also are the same whether O 2 or NO 3 was used as an electron acceptor. Combining data measured under both O 2 ‐ and NO 3 ‐reducing conditions, an isotopic enrichment value ( ε ) of −25.8 ± 1.6‰ is measured for the microbial culture during 1,2‐DCA degradation. The ε ‐value can be converted into a kinetic isotope effect (KIE) value to relate the observed isotopic fractionation to the mechanism of degradation. This KIE value (1.05) is consistent with degradation via hydrolytic dehalogenation under both electron‐accepting conditions. This study demonstrates the added value of compound‐specific isotope analysis not only as a technique to verify the occurrence and extent of biodegradation in the field, but also as a natural reaction probe to provide insight into the enzymatic mechanism of contaminant degradation.

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Marine Environmental Genomics: Unlocking the Ocean's Secrets - Robert Edwards; Elizabeth Dinsdale (Oceanography, 2007)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

PHYSIOLOGICAL AND BEHAVIORAL DEVELOPMENT IN DELPHINID CALVES: IMPLICATIONS FOR CALF SEPARATION AND MORTALITY DUE TO TUNA PURSE‐SEINE SETS - Shawn R. Noren; Elizabeth F. Edwards (Marine Mammal Science, 2007)
Tuna purse‐seiners in the eastern tropical Pacific (ETP) capture yellowfin tuna by chasing and encircling herds of associated dolphins. This fishery has caused mortality in 14 dolphin species (20 stocks) and has led to significant depletions of at least three stocks. Although observed dolphin mortality is currently low, set frequency remains high and dolphin stocks are not recovering at expected rates. Mortality of nursing calves permanently separated from their mothers during fishery operations may be an important factor in the lack of population recovery, based on the recent discovery that calves do not accompany 75%–95% of lactating females killed in the purse‐seine nets. We assessed age‐specific potential for mother–calf separations and subsequent mortality of calves by reviewing and synthesizing published data on physiological and behavioral development in delphinids from birth through 3 yr postpartum. Results indicate that evasive behavior of mothers, coupled with the developmental state of calves, provides a plausible mechanism for set‐related mother–calf separations and subsequent mortality of calves. Potential for set‐related separation and subsequent mortality is highest for 0–12‐mo‐old dolphins and becomes progressively lower with age as immature dolphins approach adult stamina and attain independence.

Erratum to: Cervical cancer-causing human papillomaviruses have an alternative initiation site for the L1 protein - Elizabeth Webb; John Cox; Stirling Edwards (Virus Genes, 2006)

Sensitivity of Marine‐Reserve Design to the Spatial Resolution of Socioeconomic Data - ELIZABETH A. RICHARDSON; MICHEL J. KAISER; GARETH EDWARDS‐JONES; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Socioeconomic considerations should have an important place in reserve design. Systematic reserve‐selection tools allow simultaneous optimization for ecological objectives while minimizing costs but are seldom used to incorporate socioeconomic costs in the reserve‐design process. The sensitivity of this process to biodiversity data resolution has been studied widely but the issue of socioeconomic data resolution has not previously been considered. We therefore designed marine reserves for biodiversity conservation with the constraint of minimizing commercial fishing revenue losses and investigated how economic data resolution affected the results. Incorporating coarse‐resolution economic data from official statistics generated reserves that were only marginally less costly to the fishery than those designed with no attempt to minimize economic impacts. An intensive survey yielded fine‐resolution data that, when incorporated in the design process, substantially reduced predicted fishery losses. Such an approach could help minimize fisher displacement because the least profitable grounds are selected for the reserve. Other work has shown that low‐resolution biodiversity data can lead to underestimation of the conservation value of some sites, and a risk of overlooking the most valuable areas, and we have similarly shown that low‐resolution economic data can cause underestimation of the profitability of some sites and a risk of inadvertently including these in the reserve. Detailed socioeconomic data are therefore an essential input for the design of cost‐effective reserve networks.

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Are Findings from Studies of Obesity and Prostate Cancer Really in Conflict? - Stephen J. Freedland; Edward Giovannucci; Elizabeth A. Platz (Cancer Causes & Control, 2006)

Evaluating Wolf Translocation as a Nonlethal Method to Reduce Livestock Conflicts in the Northwestern United States - ELIZABETH H. BRADLEY; DANIEL H. PLETSCHER; EDWARD E. BANGS; KYRAN E. KUNKEL; DOUGLAS W. SMITH; CURT M. MACK; THOMAS J. MEIER; JOSEPH A. FONTAINE; CARTER C. NIEMEYER; MICHAEL D. JIMENEZ (Conservation Biology, 2005)
Successful nonlethal management of livestock predation is important for conserving rare or endangered carnivores. In the northwestern United States, wolves ( Canis lupus ) have been translocated away from livestock to mitigate conflicts while promoting wolf restoration. We assessed predation on livestock, pack establishment, survival, and homing behavior of 88 translocated wolves with radiotelemetry to determine the effectiveness of translocation in our region and consider how it may be improved. More than one‐quarter of translocated wolves preyed on livestock after release. Most translocated wolves (67%) never established or joined a pack, although eight new packs resulted from translocations. Translocated wolves had lower annual survival (0.60) than other radio‐collared wolves (0.73), with government removal the primary source of mortality. In northwestern Montana, where most wolves have settled in human‐populated areas with livestock, survival of translocated wolves was lowest (0.41) and more wolves proportionally failed to establish packs (83%) after release. Annual survival of translocated wolves was highest in central Idaho (0.71) and more wolves proportionally established packs (44%) there than in the other two recovery areas. Translocated wolves showed a strong homing tendency; most of those that failed to home still showed directional movement toward capture sites. Wolves that successfully returned to capture sites were more likely to be adults, hard (immediately) rather than soft (temporarily held in enclosure) released, and translocated shorter distances than other wolves that did not return home. Success of translocations varied and was most affected by the area in which wolves were released. We suggest managers translocating wolves or other large carnivores consider soft releasing individuals (in family groups, if social) when feasible because this may decrease homing behavior and increase release‐site fidelity.

Plasma insulin-like growth factor-1 and binding protein-3 and subsequent risk of prostate cancer in the PSA era - Elizabeth A. Platz; Michael N. Pollak; Michael F. Leitzmann; Meir J. Stampfer; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2005)

Milk thistle and indinavir: a randomized controlled pharmacokinetics study and meta-analysis - Edward Mills; Kumanan Wilson; Mike Clarke; Brian Foster; Scott Walker; Beth Rachlis; Nick DeGroot; Victor M. Montori; Wayne Gold; Elizabeth Phillips; Stephen Myers; Keith Gallicano (European Journal of Clinical Pharmacology, 2005)

A national framework for cancer surveillance in the United States - Phyllis A. Wingo; Holly L. Howe; Michael J. Thun; Rachel Ballard-Barbash; Elizabeth Ward; Martin L. Brown; JoAnne Sylvester; Gilbert H. Friedell; Linda Alley; Julia H. Rowland; Brenda K. Edwards (Cancer Causes & Control, 2005)

Molecular Analysis of the Relatedness of Five Domesticated Turkey Strains - Edward J. Smith; Tuoyu Geng; Elizabeth Long; F. William Pierson; D. Phillip Sponenberg; Cal Larson; Robert Gogal (Biochemical Genetics, 2005)

Cervical Cancer-causing Human Papillomaviruses have an Alternative Initiation Site for the L1 Protein - Elizabeth Webb; John Cox; Stirling Edwards (Virus Genes, 2005)

Perchlorate‐reducing microorganisms isolated from contaminated sites - Alison S. Waller; Evan E. Cox; Elizabeth A. Edwards (Environmental Microbiology, 2004)
Summary An extensive microcosm survey of perchlorate‐contaminated sites was undertaken to assess the ability of indigenous microorganisms to degrade perchlorate. Samples from 12 contaminated sites and from one pristine location were analysed. Perchlorate was degraded to below detection limit in all electron donor‐amended microcosms. Perchlorate‐reducing microorganisms (PRMs) were numerous at most of these sites. Sixteen distinct PRMs were isolated that were phylogenetically related to either Dechloromonas in the Beta Proteobacteria (9/16 isolates) or to Azospirillum in the Alpha Proteobacteria (7/16 isolates). The majority of previously isolated PRMs are in the Beta Proteobacteria related to Dechloromonas or Dechlorosoma . This study indicates that PRMs of the genus Azospirillum may be more prevalent at contaminated sites than the current record of isolates suggests. Cell yields, electron donor to perchlorate ratios and maximum specific growth rates were similar among the isolates and similar to the few previously published values. However, the Monod half‐saturation constants for perchlorate for the two Azospirillum isolates characterized were lower than those measured for other genera, suggesting that they may be more effective at low concentrations of perchlorate. These results extend the current understanding of PRMs from diverse environments and provide added confidence that microbial perchlorate reduction is ubiquitous, even at highly contaminated sites, and can be harnessed effectively for bioremediation.

Plasma 1,25-Dihydroxy- and 25-Hydroxyvitamin D and Subsequent Risk of Prostate Cancer - Elizabeth A. Platz; Michael F. Leitzmann; Bruce W. Hollis; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2004)

Failure to detect prostate cancer in the PSA era: comments on N Engl J Med 2003; 349: 215–224 and N Engl J Med 2003; 349: 335–342 - Elizabeth A. Platz; Angelo M. De Marzo; Edward Giovannucci (Cancer Causes & Control, 2004)

The information and support needs of women at high risk of familial breast and ovarian cancer: how can cancer genetic services give patients what they want? - Rachel Iredale; Kate Brain; Liz Edwards; Jonathon Gray; Elizabeth France (Familial Cancer, 2003)

Effects of ultraviolet radiation on toad early life stages - Edward E. Little; Robin D. Calfee; David L. Fabacher; Cynthia Carey; Vicki S. Blazer; Elizabeth M. Middleton (Environmental Science and Pollution Research, 2003)

Physiological and molecular characterization of anaerobic benzene‐degrading mixed cultures - Ania C. Ulrich; Elizabeth A. Edwards (Environmental Microbiology, 2003)
Summary Nine distinct anaerobic benzene‐degrading cultures were enriched from sediment samples from four different sites. These cultures used nitrate, sulphate or CO 2 as electron acceptors. The shortest doubling times were observed in nitrate‐reducing cultures, although cell yield was lowest in these cultures. The highest substrate concentration utilized and maximum absolute rates of benzene degraded (in µM day −1 ) were observed in methanogenic cultures. The microbial compositions of a methanogenic and nitrate‐reducing culture were determined from a clone library of 16S rRNA genes. Five Bacterial 16S rRNA sequences, one of which resembled a clone previously found in a sulphate‐reducing, benzene‐degrading culture and four Archaeal 16S rRNA sequences were identified in a methanogenic culture. Four Bacterial and no Archaeal 16S rRNA sequences were identified in a nitrate‐reducing culture. The relative abundance of the four nitrate‐reducing putative species was determined by slot blot hybridization. Two green sulphur bacteria together formed 52% of the clone library, but were found to be less than 4% of the culture by slot blot analysis. One of the cloned 16S rRNA gene sequences comprised 70% of the culture and was phylogenetically 93% similar to both Azoarcus and Dechloromonas species, which have been shown to degrade aromatic compounds, including benzene, under nitrate‐reducing conditions.

Monitoring the Penetration Enhancer Dimethyl Sulfoxide in Human Stratum Corneum in Vivo by Confocal Raman Spectroscopy - Peter J. Caspers; Adrian C. Williams; Elizabeth A. Carter; Howell G. M. Edwards; Brian W. Barry; Hajo A. Bruining; Gerwin J. Puppels (Pharmaceutical Research, 2002)

Evaluating Ultraviolet Radiation Exposure with Satellite Data at Sites of Amphibian Declines in Central and South America - Elizabeth M. Middleton; Jay R. Herman; Edward A. Celarier; John W. Wilkinson; Cynthia Carey; Robert J. Rusin (Conservation Biology, 2001)
Many amphibian species have experienced substantial population declines or have disappeared altogether during the last several decades at a number of amphibian survey sites in Central and South America. Our study addresses the use of trends in solar UV‐B radiation exposure (280–320 nm) at these sites over the last two decades, derived from the Total Ozone Mapping Spectrometer satellite data. It is intended to demonstrate a role for satellite observations in determining whether UV‐B radiation is a contributing factor in amphibian declines. We used these data to calculate the daily erythemal (sunburning) UV‐B, or UV‐B ery , exposure at the latitude, longitude, and elevation of each of 20 survey sites. The annually averaged UV‐B ery dose, as well as the maximum values, have been increasing in both Central and South America, with higher levels reached at the Central American sites. The annually averaged UV‐B ery exposure increased significantly from 1979–1998 at all 11 Central American sites we examined ( r 2 = 0.60–0.79; p ≤ 0.015), with smaller but significant increases at five of the nine South American sites ( r 2 = 0.24–0.42; p ≤ 0.05). The number of days having the highest UV‐B exposure (≥6.75 kJ/m 2 /day) increased in both regions from r 2 = 0.24–0.42; p ≤ 0.001). In Central America, the contribution of these very high UV‐B ery exposure levels to the annual UV‐B ery total increased from approximately 5 to approximately 15% over the 19‐year period, but actual daily exposures for each species are unknown. A UV‐B ratio, the highest monthly UV‐B exposure relative to the annual average for the highest UV‐B category (≥6.75 kJ/m 2 ), increased in both regions over this time period ( r 2 = 0.73; p ≤ 0.001). This UV index was consistently higher for Central America, where species declines have been the most severe. These results should justify further research into whether UV‐B ery radiation plays a role in amphibian population declines and extinctions. We discuss synergy among UV‐B radiation and other factors, especially those associated with alterations of water chemistry (e.g., acidification) in aqueous habitats.

Cumulative exposure to tamoxifen: DNA adducts and liver cancer in the rat - Philip Carthew; Peter Lee; Richard Edwards; Robert Heydon; Barbara Nolan; Elizabeth Martin (Archives of Toxicology, 2001)

TUMOR-ASSOCIATED ANTIGEN EXPRESSION AND GROWTH REQUIREMENTS PREDICT TUMORIGENESIS IN SQUAMOUS CELL CARCINOMA - EDWARD R. SAUTER; DAVID TICHANSKY; E. ELIZABETH FURTH; MEENHARD HERLYN (In Vitro Cellular & Developmental Biology - Animal, 2001)

Bowel movement, use of laxatives and risk of colorectal adenomatous polyps among women (United States) - Laurent Elizabeth A. Dukas; Graham A. Colditz; Walter C. Willett; Edward L. Giovannucci (Cancer Causes & Control, 2000)

Proportion of colon cancer risk that might be preventable in a cohort of middle-aged US men - Elizabeth A. Platz; Walter C. Willett; Graham A. Colditz; Eric B. Rimm; Donna Spiegelman; Edward Giovannucci (Cancer Causes & Control, 2000)

Glycosylated hemoglobin and risk of colorectal cancer and adenoma (United States) - Elizabeth A. Platz; Susan E. Hankinson; Nader Rifai; Graham A. Colditz; Frank E. Speizer; Edward Giovannucci (Cancer Causes & Control, 1999)

Parity and other reproductive factors and risk of adenomatous polyps of the distal colorectum (United States) - Elizabeth A. Platz; Maria Elena Martinez; Francine Grodstein; Charles S. Fuchs; Graham A. Colditz; Meir J. Stampfer; Edward Giovannucci (Cancer Causes & Control, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The effects of ochratoxin A on postimplantation rat embryos in culture - K. Mayura; John F. Edwards; Elizabeth A. Maull; Timothy D. Phillips (Archives of Environmental Contamination and Toxicology, 1989)